Bioluminescent Multi-Characteristic Opsin for Simultaneous Optical Stimulation and Continuous Monitoring of Cortical Activities - Narcisse, Darryl; Mustafi, Sourajit Mitra; Carlson, Michael; Batabyal, Subrata; Kim, Sanghoon; Wright, Weldon; Kumar Mohanty, Samarendra (Frontiers in Cellular Neuroscience, 2021)
Stimulation and continuous monitoring of neural activities at cellular resolution is required for understanding of the sensory processing of stimuli and development of effective neuromodulation therapies. We present Multi-Characteristic Opsin (bMCOII), a hybrid optogenetic actuator and bioluminescence Ca2+-sensor for excitation free, continuous monitoring of neural activity in the visual cortex with high spatio-temporal resolution. Exceptionally low intensity (10 μW/mm2) light could elicit neural activation that could be detected by the Ca2+-bioluminescence imaging. Uninterrupted (>14 hours) recording of visually evoked neural activity in the cortex of mice enabled determination of strength of sensory activation. Further, Artificial Intelligence based Neural Activation Parameter transformed the Ca2+-bioluminescence signals to network activity patterns. During continuous Ca2+-bioluminescence recordings, visual cortical activity peaked at the 7th-8th hour of anesthesia, coinciding with circadian rhythm. For both direct optogenetic stimulation in cortical slices and visually evoked activities in visual cortex, we observed secondary delayed Ca2+-bioluminescence responses, suggesting involvement of neuron-astrocyte-neuron pathway. Our approach will enable development of a modular and scalable interface system with the capability to serve a multiplicity of applications to modulate and monitor large-scale activities in brain.